ANALISIS PERANCANGAN UI UX SEBAGAI VISUALISASI PENILAIAN KINERJA KARYAWAN BIRENTCAR BERBASIS WEBSITE - Sally Febriana Monica; Anjik Sukmaaji; Nunuk Wahyuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
One of the business processes carried out by company is employee performance appraisal. However, the performance appraisal system at this company is still done manually in several ways. However, the problem is that there is no website that has a display that is easily accessible for employees so that business processes do not run properly and hinder the work of employees. The right design of a website that provides information and displays that are easily accessible can help employees work related to managing employee performance information. Based on these problems, this research has conducted an analysis to increase employee interest in using websites and designing UI/UX designs as a website-based employee application visualization. A comfortable and easy-to-reach UI/UX design will attract users' interest. The User Centered Design method is a method used to design a design based on its users, namely employees and admins, which is expected to be a way out for Perusahaan to escape the problem. Evaluate the design results using usability testing with an average result of 84.5% resulting in a design that is in accordance with user needs.